Climate change and water in the UK: Recent scientific evidence for past and future change. (April 2017) - Garner, Grace; Hannah, David M; Watts, Glenn
A changing climate is anticipated to alter hydroclimatological and hydroecological processes across the UK and around the world. This paper builds on a series of reports commissioned in 2012 (Water Climate Change Impacts Report Card [WCCRC], 2012) and published in a special issue of Progress in Physical Geography in 2015 that interpreted and synthesised the relevant, peer-reviewed scientific literature of climate change impacts on the UK's water environment. It aims to provide reliable, clear information about the potential impacts of climate change on hydrology and the water environment. We review new evidence since 2012 for historical and potential future changes in precipitation and evapotranspiration, river flows and groundwater levels, river and groundwater temperature/quality and, finally, aquatic ecosystems. Some new evidence exists for change in most of these hydrological components, typically in support of the spatial and temporal trends reported in WCCRC 2012. However, it remains the case that more research has been conducted on rainfall and river flows than evapotranspiration, groundwater levels, river and groundwater temperature, water quality or freshwater ecosystems. Consequently, there remains a clear disparity of robust evidence for historical and potential future change between the top and bottom of the hydroclimatological–hydroecological process chain. As was the case in WCCRC 2012, this remains a significant barrier to informed climate change adaptation in these components of the water environment.